Changes in Local Atrial Electrograms and Surface ECG Induced by Acute Atrial Myocardial Infarction - Amorós-Figueras, Gerard; Roselló-Diez, Elena; Sanchez-Quintana, Damian; Casabella-Ramon, Sergi; Jorge, Esther; Nevado-Medina, Jorge; Arzamendi, Dabit; Millán, Xavier; Alonso-Martin, Concepción; Guerra, Jose M.; Cinca, Juan (Frontiers in Physiology, 2020)
Background Atrial coronary branch occlusion is a hardly recognizable clinical entity that can promote atrial fibrillation. The low diagnostic accuracy of the ECG could deal with the characteristics of the ischemia-induced changes in local atrial electrograms, but these have not been described. Objectives We analyzed the effects of selective acute atrial branch occlusion on local myocardial structure, atrial electrograms, and surface ECG in an experimental model close to human cardiac anatomy and electrophysiology. Methods Six anesthetized open-chest anesthetized pigs underwent surgical occlusion of an atrial coronary branch arising from the right coronary artery during 4 h. Atrial electrograms and ECG were simultaneously recorded. One additional pig acted as sham control. In all cases, the hearts were processed for anatomopathological analysis. Results Atrial branch occlusion induced patchy atrial necrosis with sharp border zone. During the first 30 min of occlusion, atrial electrograms showed progressive R wave enlargement (1.8 ± 0.6 mV vs. 2.5 ± 1.1 mV, p < 0.01), delayed local activation times (28.5 ± 8.9 ms vs. 36.1 ± 16.4 ms, p < 0.01), ST segment elevation (−0.3 ± 0.3 mV vs. 1.0 ± 1.0 mV, p < 0.01), and presence of monophasic potentials. Atrial ST segment elevation decreased after 2 h of occlusion. The electrical border zone was ∼1 mm and expanded over time. After 2 h of occlusion, the ECG showed a decrease in P wave amplitude (from 0.09 ± 0.04 mV to 0.05 ± 0.04 mV after 165 min occlusion, p < 0.05) and duration (64.4 ± 8.0 ms vs. 80.9 ± 12.6 ms, p < 0.01). Conclusion Selective atrial branch occlusion induces patchy atrial infarction and characteristic changes in atrial activation, R/S wave, and ST segment that are not discernible at the ECG. Only indirect changes in P wave amplitude and duration were appreciated in advanced stages of acute coronary occlusion.